Delimitacion de Neobuxbaumia mezcalaensis y N. Multiareolata (Cactaceae) con base en analisis multivariados - Arroyo-Cosultchi, G.=700 1 Terrazas, T.; Arias, S.; Lopez Mata, L.
(Es, En)
Ilus., 57 ref.
Keywords: METODOS ESTADISTICOS; IDENTIFICACION; CACTACEAE; MEXICO; NEOBUXBAUMIA MEZCALAENSIS; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO